A new method for testing non-porous surfaces for their antimicrobial efficacy using an aerosol-generating spray chamber - Poelzl, Sabine; Dreisiebner, Daniela; Zarschenas, Eva; Nokhbehzaeim, Rozita; Kittinger, Clemens (Frontiers in Microbiology, 2025)
The application of antimicrobial surfaces requires proof of their effectivity by in vitro methods in laboratories. One of the most common test methods is ISO 22196:2011, which represents a simple and inexpensive protocol by applying the bacterial suspension with known volume and concentration covered under a polyethylene film on the surfaces. The incubation is then conducted under defined humidity conditions for 24 h. Another approach for testing non-porous surfaces is the newly published ISO 7581:2023. With this protocol, a “dry test” is achieved by spreading and drying 1 μL of a bacterial suspension on the surfaces. A comprehensive evaluation of both standard protocols was conducted. This showed that they have some limitations and often do not include realistic test conditions that refer to the final product. Accordingly, the objective of this study was to develop a novel testing procedure that uses the spraying of a suspension inside of a chamber to generate aerosols with a precisely defined bacterial or yeast load. The samples to be analyzed are covered with small droplets that dry up within a few minutes and thus enable very reproducible contamination of the surfaces. The test series was carried out with low-alloyed carbon steel and glass without antimicrobial substances against two different Escherichia coli and Staphylococcus epidermidis strains and one Candida albicans strain to evaluate the new method. The results provided reproducible and reliable results in the setup carried out. This test method represents a valuable alternative for the assessment of non-porous surfaces in a manner that more closely reflects real-world conditions (e.g., simulation of aerosol formation by sneezing).